2024
DOI: 10.26434/chemrxiv-2024-2zt43
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scaling Laws for Optimal Turbulent Flow in Tree-Like Networks with Smooth and Rough Tubes and Power-Law Fluids

Ashish Garg,
Himanshu Mishra,
Jayati Sarkar
et al.

Abstract: In this study, we develop a comprehensive analytical framework to derive the optimal scaling laws for turbulent flows within tree-like self-similar branching networks, integrating a non-Newtonian power-law fluid model with index $n$. Our analysis encompasses turbulent flows occurring in both smooth and rough tubes under constraints of network's tube-volume and tube surface area. We introduce the non-dimensional conductance parameter $E$ to quantify flow conditions, investigating its variations with diameter ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Expanding upon Murray's application of the principle of minimum work in circular tubes [25], researchers have investigated flow dynamics in tree-like branching networks. For instance, Revellin et al [26] extended Murray's law to analyze non-Newtonian power-law fluid flow in two channels, revealing a constant diameter ratio (D (k+1) /D k = 2 −1/3 ) for the optimal flow irrespective of the fluid's power-law index n. Advancements by Garg et al [1,27,28] delved into networks with varying branching numbers and power-law indices, examining circular and elliptical cross-sections under volume and surface area constraints for both laminar and turbulent flows. Notably, in the laminar flow regime, Garg et al [1,27] discovered that under volume constraints, the optimal radius/diameter/length relationship remains consistent regardless of the fluid's shear-thinning or shear-thickening behavior, denoted as (D (k+1) /D k ) * = N −1/3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expanding upon Murray's application of the principle of minimum work in circular tubes [25], researchers have investigated flow dynamics in tree-like branching networks. For instance, Revellin et al [26] extended Murray's law to analyze non-Newtonian power-law fluid flow in two channels, revealing a constant diameter ratio (D (k+1) /D k = 2 −1/3 ) for the optimal flow irrespective of the fluid's power-law index n. Advancements by Garg et al [1,27,28] delved into networks with varying branching numbers and power-law indices, examining circular and elliptical cross-sections under volume and surface area constraints for both laminar and turbulent flows. Notably, in the laminar flow regime, Garg et al [1,27] discovered that under volume constraints, the optimal radius/diameter/length relationship remains consistent regardless of the fluid's shear-thinning or shear-thickening behavior, denoted as (D (k+1) /D k ) * = N −1/3 .…”
Section: Introductionmentioning
confidence: 99%
“…However, under surface area constraints, this relationship becomes significantly influenced by the power-law index, expressed as (D (k+1) /D k ) * = N −(n+1)/(3n+2) . For turbulent flow, Garg et al [28] identified scaling pat- terns for smooth and rough tube networks, respectively described as…”
Section: Introductionmentioning
confidence: 99%
“…During application, the lacquer flows through channels, tubes, and sometimes into porous materials like wood. These pores can be visualized as a simplified network of tiny channels, resembling a tree structure [13][14][15][16][17]. As the lacquer enters these pores, its flow properties, particularly viscosity and surface tension, significantly impact how it fills the network and interacts with the pore walls.…”
Section: Introductionmentioning
confidence: 99%
“…Further when the lacquer is applied to a very porous material, like some types of wood, the lacquer interact with the network of tiny pores within the material. These pores could be viewed as a simplified version of a tree-like network [11][12][13][14][15]. As the lacquer penetrates the pores, its flow properties (viscosity, surface tension) would influence how it fills the network and interacts with the pore walls.…”
Section: Introductionmentioning
confidence: 99%